The Importance of Balancing the Knowledge of Fardhu 'Ain and Fardhu Kifayah According to Imam Al-Ghazali - Muhammad Husni; Kholili Hasib (Al-Munawwarah: Journal of Islamic Education, 2025)
The rapid changes in the era and the development of the modern world often result in an imbalance in prioritizing the types of fardu kifayah and fardu ‘ain knowledge. Many educational institutions prioritize the science of Fardu kifayah, often neglecting the Fardu ‘ain aspect. This study aims to explore Imam Al-Ghazali's thoughts on the importance of balance between the science of Fardu ‘ain and Fardu kifayah in the context of Islamic education. This study uses a qualitative approach with a literature study, which examines the works of Imam Al-Ghazali, especially those related to education and science. The results of the study show that Imam Al-Ghazali's thoughts on the balance of Fardu ‘ain and Fardu kifayah knowledge are very relevant to the challenges of today's Islamic education. In a modern context, Islamic education needs to integrate these two types of knowledge in order to produce a generation that is not only intellectually intelligent but also has a noble character and is responsible for building society. This study suggests that the current Islamic education curriculum integrates religious and worldly knowledge, strengthens character education, and utilizes technology as a means to achieve a balance of knowledge. Thus, Islamic education can form a generation that excels in the fields of science and morals and plays an active role in the development of the community and civilization.